Teaching interactive skills in mixed ability classes - Nilufarxon Tillaboyeva Rasuljanovna; Hakimova Muattarhon Muhiddinovna (Zien Journals, 2022)
The aims of essay are to find out what resource literature says about how English teachers should work in large mixed-ability classes to make sure they help all students improve their English and also to find out what views three upper secondary English teachers have on how to reach all students. I have chosen to limit the area I am going to investigate by focusing on upper secondary English teachers and how they need to work to help the weaker students in mixed ability classes.
Keywords: mixed-ability classes; interests; ability; motivation